Exploring Semantic Component and Expansion: Unpacking the Layers of Meaning in “Kung Tuyo Na Ang Luha Mo, Aking Bayan” by Amado V. Hernandez - Martin, Mar Fernandez; Atacador, Cristian Gregor E (Universitas Muria Kudus, 2025)
This study explores the semantic components and expansions of “Kung Tuyo na ang Luha Mo, Aking Bayan,” focusing on the linguistic experiences of the author in the poem, semantic components, semantic expansion, and implications in education. Relational qualitative content analysis was utilized to unpack the poem systematically. The findings highlight significant semantic components and expansion in line/s such as “Lumuha ka, aking bayan; buong lungkot mo iluha”, Personification, depicted as a person crying, symbolizing national grief under colonial oppression, additionally, “Katulad mo ay si Huli, naaliping bayad-utang, katulad mo ay si Sisa, binaliw ng kahirapan”, Simile, the nation is compared to Rizal’s tragic characters Juli and Sisa, symbolizing suffering under colonial and systemic oppression. Moreover, with words/phrases like